Typical Features Contrast of Hot Water Flooding and Steam Flooding - LI Fang-Fang; SHI Changlin; Yao Weiying; GAO Zhenglong; WU Wei; LIU Shanshan (International Journal of Petroleum Technology, 2018)
Steam flooding and hot water flooding are the two main important thermal recovery methods for heavy oil reservoirs. Due to physicochemical properties difference of steam and hot water, the mechanism and production performance of hot water and steam flooding vary greatly. In this paper, steam and hot water flooding experiments under different temperature were conducted using Qi 40 heavy oil in Liaohe Oilfield in China to obtain typical features such as displacement efficiency, relative permeability, water cut and dimensionless productivity index of the two. The results show that steam and hot water flooding performance are quite different from each other under the same temperature. Compared with water flooding, displacement efficiency of steam flooding is 8.98%, 10.97% higher under 100℃ and 200℃ respectively, in addition, oil relative permeability is much higher and residual oil saturation is much lower at the same temperature. Water state and temperature are main reasons of displacement efficiency, relative permeability and productivity index difference; vapor state and higher temperature resulting in higher oil recovery, oil relative permeability and oil production index.